IMPACT OF SEAWEED SAPS ON GROWTH, FLOWERING BEHAVIOR AND YIELD OF SOYBEAN [GLYCINE MAX (L.) MERRILL.] - K. K. LODHI; N. K. CHOUBEY; S. K. DWIVEDI; A. PAL; P. C. KANWAR (The Bioscan, 2015)
A field experiment was conducted during the Kharif season of 2013 at Research cum Instructional Farm of Indira Gandhi Krishi Vishwavidyalaya, Raipur (Chhattisgarh) to study the effects of seaweed saps on growth, flowering behavior and yield of Soybean in Vertisol of Chhattisgarh. The foliar spray was applied three sprays at different concentrations (0, 2.5, 5.0, 7.5, 10 and 15% v/v) of seaweed extracts (namely Kappaphycus and Gracilaria) at different days (25, 50 and 75 days) after sowing. Foliar applications of seaweed extract were found significantly impact on growth, flowering behavior and yield. Among all the treatments 15% Kappaphycus sap + recommended dose of nutrient (RDN) increased the plant height (90.50 cm), dry matter accumulation (40.32 g plant-1), pod setting index (87.35 %), number of pods plant-1 (93.43) and 100 seed weight (10.37g). The lowest number of drop flower plant-1 (13.3) was obtained under treatment 15% K sap + RDN (T4). The highest seed yield (25.10 q ha-1) was recorded with applications of 15% Kappaphycus sap + RDN, followed by 15% Gracilaria sap + RDN (24.30 q ha-1)extract resulting in an increase by 58.25% and 53.21% seed yield, respectively compared to the control (Water spray + RDN) seed yield (15.86 q ha-1).